Makna Tersembunyi Pada Video Klip “Jiwa Yang Bersedih” Milik Ghea Indrawari - Sejati, Taqwa; Wijaya, Edi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Video clips are a means of promotion and expression for those involved in the world of entertainment everywhere, including in Indonesia. The discussion in this research is Ghea Indrawari's video clip, directed by Joshua Axel Limandjaja on the record label Hits Records. This research is a type of descriptive qualitative research which uses a communication science approach, specifically focusing on mass communication, one of the objects of research is the video clip in question. Meanwhile, the data collection method used in this research is Ferdinand Saussure's semiotic theory, observation is also of course documentation to strengthen and serve as authentic evidence. Otherwise, the sources for this research also came from the researcher's book, search results from several research supporting articles on confirmed website pages as well as supporting documents both outside the network and on other networks. The next step is that the collected data is immediately analyzed. The results of the analysis are data education regarding the theory used, explanation and conclusions.